Food intake monitoring and management system for athletes / Nursyahira Azeanty Ruhaizak … [et al.] - Ruhaizak, Nursyahira Azeanty; Yusoh, Syarifah Diyanah; Ahmadon, Fadzlin; Jasmis, Jamaluddin; Aminuddin, Raihah (Faculty of Computer and Mathematical Sciences, 2023)
At UiTM Campus Shah Alam, athletes who have taken the course Nutrition for Exercise and Health (SPS220) must monitor and manage their daily food intake. The lecturer for the course will keep an eye on the student's food intake. It is important for the athlete to monitor their Body mass index (BMI) thus they can monitor their health and perform better in any sports they take part in. The lecturer can suggest meals for the athletes that are appropriate for their needs before, during, and after training and tournaments using the data given by the athletes. However, the existing approach makes it difficult for the lecturer to store and monitor the athlete's information. It is tedious for the lecturer to store the information, and there may be a risk of missing data. Therefore, a web-based system for the athlete and lecturer to monitor and manage the food intake taken by the athlete is developed. Athletes can upload information into the system, which lecturers are monitoring, such as their weight, height, and daily food intake. The system kept the data in an online database. The system allows athletes to input, view, update, and remove their daily food intake and monitor their BMI. Then the lecturers can monitor and update their comments for the athletes based on their meals. The system can be assessed online. In the future, the system can include a visualization chart based on the athlete's BMI, food intake calorie calculations based on carbohydrates (CHO), protein, and fat, and meal plans to manage the athlete's meal intake.